The financial professional's guide to healthcare reform - Dietrich, Mark O. (Wiley, 2012)
The Financial Consultants'Guide to Healthcare Reform provides an historical backdrop on how the healthcare system got to its present state including the Massachusetts Reform and Medicare Advantage along with an explanation of the principal types of health insurance in the United States and how "insurance" actually works. A review and explanation of each of the reform provisions follows, including an analysis of what the implications are for providers, consumers and business and what responses each of these communities might have to the Reform